Translation methods in the indonesian-english “lutung kasarung” story - Wahyuni, Ni Luh Putu Richa; Jayantini, I Gusti Agung Sri Rwa; Suastini, Ni Wayan (Journal of Language and Applied Linguistics, 2022)
The study aims to analyze the types of translation methods in the bilingual story. The data source of this research is Lutung Kasarung published in 2019 which was retold by Lilis Hu and translated to English by M. J. L. Jordon. Qualitative research is used as a research method which describes the data descriptively. In classifying the data, this study used Newmark’s theory (1988) to analyze the data. This study found that word-for-word translation has 4% data, literal translation has 10% data, faithful translation has 50% data, semantic translation has 8% data, adaptation translation has 4% data, free translation has 14% data, and idiomatic translation and also communicative translation have 5% data. It found that faithful translation method is the most dominant applied method which indicates that the translation emphasizes the SL and keeps the meaning of the SL.